A SYSTEMATIC REVIEW OF TIKTOK FOR ENGLISH LANGUAGE TEACHING - Siti Waroh; Lia Pusfitasari; Naf'an Tarihoran (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This systematic review examines the role of TikTok in English Language Teaching (ELT), with particular attention to its effectiveness in enhancing motivation, vocabulary acquisition, and speaking proficiency. Using PRISMA guidelines, this study analyzed 19 peer-reviewed empirical research articles published between 2020 to 2024, indexed in Google Scholar, Scopus, ScienceDirect, Mendeley, and Taylor & Francis Online. Findings indicate that TikTok fosters self-regulated learning and student engagement while facilitating interactive pronunciation and fluency practice. However, barriers to its optimal implementation include exposure to non-educational content, the absence of systematic integration, and the lack of instructor feedback. While TikTok cannot replace conventional teaching methods, it can be a valuable supplementary tool when combined with methodical instructional techniques. Future research should investigate its long-term impact on ELT, particularly in writing and listening skills, and propose instructional strategies for its integration into formal curricula. These findings underline the need for strategic implementation in English Language Teaching classrooms to contribute to the broader discourse on using TikTok in English Language Teaching.